Disability and mild cognitive impairment: a longitudinal population-based study - Artero, Sylvaine; Touchon, Jacques; Ritchie, Karen (International journal of geriatric psychiatry, 2001)
Objective To determine whether mild cognitive deficit is associated with parallel changes in ability to perform activities of daily living. Background While considerable research has been conducted on the effect of senile dementia and other neurodegenerative disorders on ability to perform everyday activities, little is known about the much larger group of elderly persons suffering from mild cognitive deficits. Methods Disability prevalence was estimated in 368 persons over the age of 65 years recruited from the general population via a general practitioner network. Subjects were followed over a 3‐year period using computerized cognitive assessment and observations of everyday functioning. Standardized neurological assessment in the third year permitted the identification of subjects who have evolved towards dementia. Results An overall disability prevalence was found in the general population of 26.3%, with 30.8% in subjects with sub‐clinical cognitive impairment. Longitudinal follow‐up showed cognitive decline over time without dementia to be paralleled by changes in activity performance, with visuospatial deficits having the most marked effect on overall functioning. High intelligence quotient (IQ) and education are seen to reduce the degree of activity loss, but only when senile dementia is not present. Conclusions Difficulties in the performance of everyday activities were found more frequently in non‐demented subjects with mild cognitive deficits than in the general population. High pre‐morbid levels of ability are seen to have a protective effect. A diagnosis of dementia should not therefore be required by persons with cognitive impairment applying for home help. Copyright © 2001 John Wiley & Sons, Ltd.